Planar arrangement of eukaryotic cells in merged hydrogels combines the advantages of 3-D and 2-D cultures - Alexander A. Gordeev; Helena V. Chetverina; Alexander B. Chetverin (BioTechniques)
We report an unordered 2-D array of eukaryotic cells completely embedded in a 3-D matrix. Every cell is located at the same distance from the gel surface, which ensures uniformity of growth conditions and ease of observation characteristic of a 2-D culture. Each cell is firmly immobilized, and each has a unique address in the array. The cells can be rapidly screened, individually monitored during extended time periods, and cultured with the formation of spheroid microcolonies characteristic of a 3-D culture. Individual microcolonies can be extracted from the gel and further propagated, thus enabling isolation of pure cell clones from rather dense cell populations and rapid drug-free generation of stable cell lines.